Kanto’s Guest House Business Competitive Strategic Analysis for Sustainable Income - Ameliya Rosita (Bina Nusantara University, 2022)
This research aims to formulate and select Kantos House (KH) - Guest House strategy to face the competitive market in hotel accommodation industry for optimizing sustainable income through (1) evaluated brand awareness of KH; (2) identified external and internal factors that significant related to KH business, (3) analyzed brand effectiveness and competitive advantages of KH for optimizing sustainable income. This research method used Kapferer’s Prism for analyzing KH brand identity, multichannel online review for analyzing consumer feedback of output average score of company’s hotel score review, room occupancy company report for analyzing average rate of KH’s occupancy, and SWOT diagram analysis. The result of this research shows currently the design of company brand has accomplished all the six criteria based on Brand Identity Prism, unfortunately the brand awareness still on low level. This resulted related due to the absence of brand marketing communication company’s budget. Customer Review currently is very important for company, which proof by the management’s commitment to maintain the average rate of KH online review at least or more than 4,4 of 5 star “very good” (Google rating version), also by opening review channels for customer feedback by putting the sticker for TripAdvisor review on the wall near the lobby hotel also via online by adding sub- menu for the review purposed. The average level of KH’s room occupancy from 2017 until November 2018 was 82% and on 2017 was 87%. This result is favorable which the company’s position highly above of the Indonesian hotel’s average room occupancy in 2017 was on 65% (BPS 2017). The SWOT analysis result showed the position of KH was in the 1st quadrant means company on healthy condition which the suitable competitive strategy is growth or aggressive strategy.